Real-world evidence of suboptimal blood pressure control in patients with type 2 diabetes. Issue 10 (October 2015) - Walraven, Iris; Mast, M. Ruth; Hoekstra, Trynke; Jansen, Aaltje P.D.; Rauh, Simone P.; Rutters, Femke R.; van der Heijden, Amber A.W.A.; Elders, Petra J.M.; Moll, Annette C.; Polak, Bettine C.P.; Dekker, Jacqueline M.; Nijpels, Giel
<x xml:space="preserve">Abstract</x> Aims: In order to eventually improve blood pressure (BP) management, the aim of this study was to identify subgroups of type 2 diabetes mellitus (T2DM) patients with distinct trajectories of SBP levels. Identifying subgroups with distinct SBP trajectories helps to better understand the course of SBP levels in T2DM patients and its associated consequences. Subgroup characteristics were determined and the prevalence of complications and mortality rates over time in the different subgroups was investigated. Methods: Five thousand, seven hundred and eleven T2DM patients with at least two SBP follow-up measurements were selected from a prospective T2DM cohort of 9849 T2DM patients. The mean follow-up period was 5.7 years (range 2–9 years). Latent Class Growth Modeling, as currently the most flexible cluster analysis available, was performed to identify subgroups of patients with distinct SBP trajectories. Subgroup characteristics were determined by multinomial logistic regression analyses. Results: Four subgroups with distinct SBP trajectories were identified. The largest subgroup (85.6%) showed adequate SBP control (at or around 140 mmHg) over time. The second subgroup (5.6%) were hypertensive in the first years, responded slowly to BP management and eventually reached SBP control. The third subgroup (3.4%) showed deteriorating hypertension during the first 4 years, then showed insufficient response to BP management. The fourth subgroup (5.4%) showed deteriorating hypertension over time. Patients within subgroups 2–4 were significantly older, comprised more women, used more antihypertensive medication and had a higher prevalence of retinopathy, microalbuminuria and cardiovascular disease (CVD) mortality. Conclusion: More than 85% reached and maintained adequate SBP control. Subgroups with a more unfavourable course of SBP control also showed higher rates of microvascular complications and CVD mortality over time. This study identified important subgroups to target in order to improve BP management in T2DM patients.